Penerapan model pembelajaran means ends analysis untuk meningkatkan keterampilan penalaran matematis pada materi keliling dan luas bangun datar peserta didik kelas V sd - Indra, Shifa Ramadhana; Poerwanti, Jenny Indrastoeti Siti (Didaktika Dwija Indria, 2026)
This study aims to improve mathematical reasoning skills in the subject of perimeter and area of flat shapes through the application of the Means Ends Analysis (MEA) learning model to fifth-grade students at Trombol 2 Public Elementary School, Mondokan, Sragen, in the 2024/2025 academic year. The research method used was qualitative, specifically Classroom Action Research, which was carried out in two cycles. Each cycle included the stages of planning, implementation, observation, and reflection. There were 16 students participating in the study. Data collection was conducted through observation, interviews, documentation, and tests. Data validity was tested through source triangulation and technique triangulation. The data analysis technique referred to the Miles and Huberman model. The results showed improvement in each cycle. The average pre-action test score was 35.5 with a classical mastery level of 0%. In cycle I, the average test score was 66 with a classical mastery level of 37.5% in the first meeting and increased to 74 with a classical mastery level of 62.5% in the second meeting. In cycle II, the average score increased to 80.5 with a classical mastery of 81.25% in the first meeting and reached an average score of 84 with a classical mastery of 87.5% in the second meeting. Based on this data, it can be concluded that the mathematical reasoning skills of fifth-grade students at Trombol 2 Public Elementary School, Mondokan, Sragen, in the 2024/2025 academic year improved after the implementation of the Means Ends Analysis (MEA) learning model.